PENGARUH UTANG LUAR NEGERI DAN PENANAMAN MODAL ASING TERHADAP PERTUMBUHAN EKONOMI INDONESIA - STIE Lhokseumawe (Sekolah Tinggi Ilmu Ekonomi Lhokseumawe, 2020)
High economic growth can be an indicator of the country's success in carrying out the wheels of development, which in the end will be fully utilized for improving the welfare of its people. This study aims to determine the effect of foreign debt and foreign investment on Indonesia's economic growth from 2005-2017. The data collected comes from annual secondary data from 2005-2017 obtained from Bank Indonesia, the Investment Coordinating Board and the Central Statistics Agency. The data obtained were then analyzed multiple linear regression using Eview 9.0 software. The results showed; 1) foreign debt has no significant effect on Indonesia's economic growth. 2) Foreign investment has no significant effect on Indonesia's economic growth